Lecturers’ Challenges and Strategies in Teaching English Writing Skills in Large Classes - Nia, Nur Ade Erma; Fithriani, Rahmah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Teaching in a class with a large number of students is a phenomenon experienced by the majority of lecturers in Indonesia. This condition obviously generates disruptions during instruction, so action is required to eliminate them.The purpose of this research is to look at the problems that arise when teaching writing skills in large classes and how to solve them from the perspective of English lecturers in Indonesia. This research is a case study using a qualitative research approach. Data collection was carried out through semi-structured interviews involving four English lecturers at four universities in North Sumatra. After the interview, the data was first transcribed, followed by thematic analysis to identify themes and answer research questions. The results of the analysis show four challenges faced by the participants in their EFL classes. All of these are related to the difficulties of: 1) providing individual assessment and feedback; 2) class and time management; 3) lack of experience and practice; and 4) lack of space, facilities, and resources. To overcome these challenges, the lecturers utilize several approaches, such as 1) using group and peer assessments, 2) using multiple approaches and analyzing student needs, 3) learning outdoors, and 4) using technology-based tools. To address these issues and make teaching large writing classes a promising endeavor, comprehensive planning and strategies must be ensured in advance according to the context and needs of students.